European Integration and Employment: A New Role for Active Fiscal Policies? - Donatella Gatti (Institute for the Study of Labor (IZA), 2002)
This paper theoretically investigates the impact of European integration on employment by developing a new-keynesian model where fiscal policy effectively reduces firms? market power. Stronger product market competition is shown to reduce the marginal ability of governments to improve employment through public consumption. As competition crowds out fiscal spending, the positive impact of markets integration on employment is weakened. Moreover, in a context where national goods? demand becomes ?global?, the marginal benefit for each national fiscal authority of increasing public consumption is lower than the marginal benefit for the community. This result stresses one source of coordination failure within the EMU.
Keywords: J41; F42; F02; E24; 330; product market integration; fiscal policy; coordination; equilibrium unemployment; Finanzpolitik; Internationale wirtschaftspolitische Koordination; Europäische Wirtschafts- und Währungsunion; Beschäftigungseffekt; Effizienzlohn; Unvollkommener Wettbewerb; Ungleichgewichtstheorie; Theorie